Postoperative neurological deficit after carotid endarterectomy: a mid-term outcome analysis - Attigah, Nicolas; Külkens, Sonja; Ringleb, Peter A.; Martin, Jochen; Allenberg, Jens-Rainer; Böckler, Dittmar (Cerebrovascular diseases, 2010)
Background: To evaluate the neurological outcome of postoperative neurological deficit (PND) in patients undergoing carotid endarterectomy (CEA). Methods: A total of 3.7% (n = 48) out of 1,290 consecutive patients developed PND and were assessed neurologically after a mid-term follow-up. Results: After a 4-year follow-up, these patients were neurologically reevaluated. Clinical assessment revealed that 48% (n = 13) of the patients had a Rankin scale score of 0 or 1, 56% (n = 14) had a National Institutes of Health Stroke Scale score of 0 or 1, and 68.5% (n = 17) reached the maximum score on the Barthel index. Conclusions: The neurofunctional prognosis of PND is good. Four years after CEA, almost half of the patients had normal or near-normal neuroclinical findings.
Gesehen am 28.11.2022